(3QSGdI eYQGL fLGI GdehMOjf hSde MjGI Gdehbfjfs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi Gdehdi GdMGce GdefRg Yf GdEOQGc hGdYOe hTcQJ YHOg GdbGFe EeGe GdCFeI hhdi GdfYe hGdcHQjGA GeG HYO aEf GdhGLH Ydi GdeQA GdYGbd hGdOjf GdaGVd Cf jchf HYbdg GdeejR dfaSg fGUMkG s
(3BNQgG (B:s
(3hEPG HdZ GdYHO GdfGUM ajeG Cedg hfhGg GdZQV hJMbb Cfg YGjf GdMb GdebJQV adjbfY HeG Sgd dg ehdGg hdjQV HeG efMg hCYWGg JeJ GdQSGdI hef hdi GdMb fQLhG GdYah hGdeZaQI hGdEbGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B68s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3abg GdePGgH GdCNQis